2010
DOI: 10.1111/j.1600-0722.2010.00743.x
|View full text |Cite
|
Sign up to set email alerts
|

CRISPLD2 polymorphisms are associated with non‐syndromic cleft lip with or without cleft palate in a northern Chinese population

Abstract: Non-syndromic cleft lip with or without cleft palate (NSCLP) is the most common craniofacial birth defect. This complex genetic disorder results from interactions between genes and environmental factors. Numerous genes have been reported in studies demonstrating association between the cleft lip and palate phenotypes and the alleles at single-nucleotide polymorphisms (SNPs) within specific genes. Recently, the cysteine-rich secretory protein LCCL domain containing 2 (CRISPLD2) has been revealed to be a novel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 17 publications
2
27
0
Order By: Relevance
“…The genomic region containing CRISPLD2 has been associated with NSCLP in Caucasian and Hispanic populations (Chiquet et al, 2007), a Northern Chinese population (Shi et al 2010) and in an American population (Letra et al, 2010). However, it was suggested that the CRISPLD2 gene did not associate with NSCLP among the Norwegian and Danish populations in Scandinavia (Jugessur et al, 2009), nor in an Irish population in Dublin (Carter et al, 2010), nor in an Italian population (Girardi et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…The genomic region containing CRISPLD2 has been associated with NSCLP in Caucasian and Hispanic populations (Chiquet et al, 2007), a Northern Chinese population (Shi et al 2010) and in an American population (Letra et al, 2010). However, it was suggested that the CRISPLD2 gene did not associate with NSCLP among the Norwegian and Danish populations in Scandinavia (Jugessur et al, 2009), nor in an Irish population in Dublin (Carter et al, 2010), nor in an Italian population (Girardi et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Shi et al (2010) reported that rs1546124 and rs4783099 were associated with CL/P in a Northern Chinese population (p 5 0.04, p 5 0.03) without Bonferroni multiple adjustments. However, we found that only the CC genotype of rs1546124 was significantly associated with CL/P (p correct 5 1.5 3 10…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations